Diabetes mellitus and prostate cancer risk in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial - Leitzmann, Michael F. (Cancer Causes Control, 2008)
OBJECTIVE: A history of diabetes has been fairly consistently related to a reduced prostate cancer risk, but previous investigations have not always addressed whether the relation with diabetes varies by prostate cancer aggressiveness or the association between diabetes and prostate cancer is modified by physical activity level and body mass, variables closely related to glucose metabolism. METHODS: We prospectively examined the diabetes–prostate cancer risk relationship among 33,088 men in the screening arm of the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. RESULTS: During 8.9 years follow-up, we ascertained 2,058 incident prostate cancer cases. Diabetes history was related to decreased risk of total prostate cancer (RR = 0.80, 95% CI = 0.68–0.95). The apparent protection afforded by diabetes was primarily due to the inverse relation with non-aggressive disease (i.e., the combination of low grade (Gleason sum <8) and low stage (clinical stages I or II); RR = 0.75; 95% CI = 0.62–0.91). In contrast, no association was noted between diabetes and aggressive disease (i.e., high grade or high stage (Gleason sum ≥8 or clinical stages III or IV); RR = 1.04, 95% CI = 0.74–1.45). In further analyses, the association between diabetes and aggressive prostate cancer was suggestively positive for men who were lean (RR = 1.64, 95% CI = 0.87–3.07; BMI < 25 kg/m(2)) and it was positive for men who were the most physically active (RR = 1.63; 95% CI = 1.07–2.62; 3+ hours vigorous activity/week). By comparison, no relations of diabetes to aggressive prostate cancer were noted for their heavier or physically less active counterparts (p-value for tests of interaction = 0.10 and 0.03 BMI and physical activity, respectively). CONCLUSION: In this study, diabetes showed divergent relations with prostate cancer by tumor aggressiveness. Specifically, diabetes was inversely associated with early stage prostate cancer but it showed no relation with aggressive prostate cancer. Exploratory analyses suggested a positive association between diabetes and aggressive prostate cancer in the subgroup of men with a low BMI.